The effects of job and personal resources on hotel employees' work engagement - Karatepe, Osman M.; Olugbade, Olusegun A. (Elsevier Sci Ltd, 2009)
Our study developed and tested a research model, which predicted the impacts of job (supervisor support) and personal resources (trait competitiveness and self-efficacy) on work engagement. Respondents were full-time employed frontline employees of the five- and four-star hotels of Abuja, the capital city of Nigeria. We used path analysis in LISREL 8.30 for testing the study hypotheses. The results demonstrated that trait competitiveness predicted three dimensions of work engagement better than did self-efficacy. That is, trait competitiveness enhanced frontline employees' feelings of vigor, dedication, and absorption, while self-efficacy significantly and positively influenced only absorption. Unexpectedly, supervisor support had no significant effects on three dimensions of work engagement. The results further revealed that frontline employees who had elevated levels of competitiveness and adequate supervisor support in the workplace had higher self-efficacy beliefs. Implications of the empirical findings and limitations are discussed in our study. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Hotel employees; Nigeria; Self-efficacy; Supervisor support; Trait competitiveness; Work engagement